Avaliação da expressão de CCL5 intracelular em linfócitos T CD8 de memória e sua relação com biomarcadores clínicos de malária vivax em crianças atendidas na Fundação de Medicina Tropical Dr. Heitor Vieira Dourado - Laco, Ana Carolina Shuan (2022)
Malaria is an infectious disease of chronic evolution, with clinical episodics manisfestations of acute profile, caused by the protozoan Plasmodium genus. The majority of cases from Amazon Region is certain by Plasmodium vivax. Althought has been considered benign and self-limit, can be worsen on children and pregnant women, having as main complications anaemia and thrombocytopnenia. The parasite has preference for young red blood cells and the parasitemia in the malaria vivax doesn´t seems to be the main cause of anaemia. In a way that the immune response modulation could be associated to this severity. The mechanisms involved in individuals with malaria are not well known. However, some studies on children with malaria has shown an association of low level of CCL5 chemokines with the increase of the disease. Objective: Our studies sought to avaliate the CCL5 expression and IFN-γ in T CD4 and T CD8 lymphocytes cells and their relation with clinical markers. Methodology: A cohort study was realized with children and teenagers from 1 to 16 years with malaria vivax at Fundação de Medicina Tropical Doutor Heitor Vieira Dourado. Were collected whole blood with heparin on day 0 (before the treatment) being acute the second phase e after that between 60 and 90 days (the convalescence phase). In each day of visit we isolated and cultivated using the antigen merozoite surface protein-1 (MSP119) and after 24 hours were realized the cells appointements. The CCL5 and IFN-γ were evaluated in T CD4+ e CD8+ CD45RO+ cells by flow cytometry. Results: We collected thirteen cases in acute phase and the second one was collected was realized in convalescence phase (after 60 to 90 days of the infection). We noted a positive correlation from de levels of hemoglobin and the percentage of TCD8+ lymphocytes memory cells IFN-γ producers on acute phase of the infection (P=0,03). In relation to RATES, when more young the individuals with malaria vivax were, less was the percentage of TCD8+ lymphocytes memory cells producers of these chemokines (P=0,04). Conclusions: The comparison of of these responses on acute phase and convalescence indicated on the correlation between the TCD8 lymphocytes memory cells rate of CCL5 and the age, suggesting an important role of the inflammatory stage in the modulation of these cells. The results are relevants indicanting that the responses founded in the studies were probably initiated on the pre erythrocyte stage and future research are importants to understand the relation of this modulation on anemia pathogenesis of malaria vivax